2017
DOI: 10.1007/s00405-016-4441-3
|View full text |Cite
|
Sign up to set email alerts
|

The association of superior attachment of uncinate process with pneumatization of middle turbinate: a computed tomographic analysis

Abstract: The frontal sinus outflow pathway is complex and can be influenced by the configuration of the uncinate process (UP). The UP can attach superior to the lamina papyracea, skull base, and middle turbinate. The factors associated with superior attachment remain unclear. This study analyzed the relationships between different types of superior UP attachment and characteristics of the surrounding structures including the agger nasi cell, skull base, and middle turbinate. This retrospective study utilized computed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 17 publications
1
14
2
Order By: Relevance
“…[17,18] Cheng et al reached somewhat similar conclusions, with no clear correlation between the existence of an AN cell and the way the UP attached superiorly. [16] Our study did, however, find just such a correlation: there was a statistically significant correlation between the attachment type of SAUP and the existence of an AN cell, when the sides with or without an AN cell were compared (29.9% vs 23.5%).…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…[17,18] Cheng et al reached somewhat similar conclusions, with no clear correlation between the existence of an AN cell and the way the UP attached superiorly. [16] Our study did, however, find just such a correlation: there was a statistically significant correlation between the attachment type of SAUP and the existence of an AN cell, when the sides with or without an AN cell were compared (29.9% vs 23.5%).…”
Section: Discussioncontrasting
confidence: 72%
“…Cheng et al reported that CB was present in 30.9% of cases, whilst Krzeski et al put the figure at 37.5%. The corresponding value in Ozcan et al was 48.1% [16,22,25] . Fadda et al used CT imaging of the paranasal sinuses from 200 individuals to show a prevalence of CB of 49.5% (69 cases).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…If not examined properly, damage to the skull base and cerebrospinal fluid rhinorrhea may possibly result. 13 Pneumatized middle concha is another frequently observed variation in the sinonasal region, with a rate of incidence of 13-73%, [14][15] subsequently exerting pressure on the middle concha and ethmoid labyrinth. 16,17 An uncinate process may also come in contact with a pneumatized middle concha, which may require surgical intervention.…”
Section: Discussionmentioning
confidence: 99%